Home based diakonia within the HIV and AIDS epidemic : towards an ecclesiology of grassroots care and identity affirmation - Snyman, Stephen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2012.